An Appraisal of the Cephalic Index in Sagittal Craniosynostosis, and the Unseen Third Dimension. Issue 1 (July 2017) - Fearon, Jeffrey A.; Ditthakasem, Kanlaya; Herbert, Morley; Kolar, John
Abstract : Background: The cephalic index is often used to evaluate sagittal craniosynostosis corrections; however, validation of this measure remains untested. Methods: A three-part study was designed to (1) determine the normal distribution of cephalic indices in untreated sagittal craniosynostosis; (2) examine index values in treated children, subsequently determined to require secondary surgery; and (3) explore the correlation between a photography-based assessment of scaphocephaly severity and the cephalic index. Results: Of 392 preoperatively measured patients (mean cephalic index, 70.7; 95 percent CI, 57.4 to 89.5), 343 (87.5 percent) had Z scores falling within 2 SD of the mean; only 49 (12.5 percent) fell more than 2 SD below the mean, whereas 13 percent exceeded the mean. For 10 patients requiring secondary surgery (mean cephalic index, 74.8; 95 percent CI, 68.1 to 83.4), the mean Z score was −0.5 (range, −2.5 to 1.6). The polled results of 10 observers revealed no significant correlation between subjectively ranked severity scores and cephalic indices. Conclusions: Although the average preoperative cephalic index in children with sagittal craniosynostosis was below normal, the majority of measurements fell within a statistically normal distribution. Furthermore, many children requiring secondary corrections were found to have relatively normal indices, suggesting that normal values are not necessarily predictive of satisfactory outcomes. We also found no correlation between this index and a subjective assessment of severity. These findings suggest that the cephalic index is not a reliable outcome measure, perhaps because of the inability for this ratio to capture the amount of correction of the reduced posterior skull height associated with sagittal craniosynostosis. CLINICAL QUESTION/LEVEL OF EVIDENCE: Diagnostic, IV.